PERFORMANCE ANALYSIS OF SHARIA AND CONVENTIONAL MUTUAL FUNDS DURING 2008 AND 2013 CRISIS PERIODS - Yudanto, Ambang Aries (JURNAL INFO ARTHA, 2016)
This research has a purpose to analyze the performance of sharia and conventional mutual funds, particularly equity mutual funds in Indonesia during 2008 and 2013 crisis periods. Within 2008 crisis period, the data set comprises of 51 equity mutual funds in which 4 were sharia mutual funds while 47 others were conventional mutual funds. Moreover, within 2013 crisis period, the data set comprises of 110 equity mutual funds in which 12 were sharia mutual funds while 98 others were conventional mutual funds. To measure the mutual funds' performance, three methods were used, which are Sharpe, Treynor, and Jensen alpha methods. Furthermore, to test whether there is any performance difference between those two types of mutual funds, the author used Mann-Whitney U test. The results indicated that in the 2008 crisis period, the entire samples cannot really withstand from the crisis. In comparison, generally the conventional equity mutual funds managed to give a better performance than the sharia equity mutual funds. Moreover, there is no performance difference between sharia and conventional equity mutual funds. Meanwhile, in the 2013 crisis period showed a more diverse result. In comparison, generally the sharia equity mutual funds managed to develop its performance during this particular crisis period compare to the previous period. Apparently, there was a performance difference between those two types of mutual funds in the 2013 crisis.Â